Diagnostic and Prognostic Value of Soluble Triggering Receptor Expressed on Myeloid Cells-1 (sTREM-1) for Septic Cardiomyopathy - Yu J; Chen Y; Pan X; Chen J; Mai Z; Zhang Y; Wang X; Zhou G; Bukhari SA; Ma D; Deng L (Dove Medical Press, 2024)
Jiamin Yu,1 Yongxia Chen,1 Xiaoyan Pan,1 Ji Chen,1 Zhenhua Mai,1 Yuanli Zhang,1 Xiaoyan Wang,2- 4 Gaosheng Zhou,5 Sayed Adam Bukhari,6 Daqing Ma,6,7 Liehua Deng1 1Department of Critical Care Medicine, Affiliated Hospital of Guangdong Medical University, Zhanjiang, 524000, People's Republic of China; 2Doctoral Scientific Research Center, Lianjiang People's Hospital, Zhanjiang, 524400, People's Republic of China; 3Affiliated Lianjiang People's Hospital, Guangdong Medical University, Zhanjiang, 524400, People's Republic of China; 4Laboratory of Southern Marine Science and Engineering, Zhanjiang, 524023, People's Republic of China; 5Department of Critical Care Medicine, The First College of Clinical Medical Science, China Three Gorges University, Yichang Central People's Hospital, Yichang, Hubei, 443003, People's Republic of China; 6Division of Anaesthetics, Pain Medicine & Intensive Care, Department of Surgery and Cancer, Faculty of Medicine, Imperial College London, Chelsea and Westminster Hospital, London, SW10 9NH, UK; 7Perioperative and Systems Medicine Laboratory, The Children's Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, Hangzhou, People's Republic of ChinaCorrespondence: Liehua Deng, Email glinson@126.comPurpose: The early diagnosis of septic cardiomyopathy remains a challenge. The present work aims to evaluate the diagnostic and prognostic value of plasma soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) levels in septic cardiomyopathy when compared with traditional myocardial biomarkers.Methods: In the 143 sepsis enrolled patients, 67 and 76 patients were classified as non-septic cardiomyopathy and septic cardiomyopathy, respectively. Their blood samples were harvested up to 14th day after hospital admission for measurements of sTREM-1 and other biomarkers, such as N-terminal pronatriuretic peptide (NT-proBNP), highly sensitive troponin (TNT-HS), myoglobin (MYO), creatine kinase isoenzyme (CK-MB), etc. All the data were collected at 8:00 a.m. The area under the receiver operating characteristic curve was obtained to assess the diagnostic accuracy of those biomarkers. The Log rank test was utilized to evaluate the prognostic value of sTREM-1 on septic cardiomyopathy.Results: Circulating sTREM-1 showed a high specificity (88.1%) and moderate sensitivity (64.5%) to distinguish patients with septic cardiomyopathy in the 143 septic patients. The diagnostic efficiency of sTREM-1 was higher than inflammatory biomarkers and traditional myocardial markers. Logistic regression revealed that plasma sTREM-1 was an independent predictor of septic cardiomyopathy. Furthermore, in the whole septic cardiomyopathy cohorts, the sTREM-1 levels in the non-survivors were significantly higher than those of survivors during ICU stay. In addition, the left ventricular systolic dysfunction had a high odds ratio (3.968) to predict 90-day mortality in septic patients with cardiomyopathy.Conclusion: High plasma sTREM-1 level may be a diagnostic marker in predicting ICU poor outcome of patients with septic cardiomyopathy.Keywords: sepsis, septic cardiomyopathy, diagnosis, sTREM-1